De héroe mártir a héroe victorioso: intelectuales peruanos frente al monumento de Francisco Bolognesi y la tesis de un proyecto primitivo para el monumento - Dias Scarelli, Rafael (Pontificia Universidad Católica del Perú, 2019)
Se presentan los posicionamientos de intelectuales y artistas peruanos frente al monumento del coronel Francisco Bolognesi en dos contextos separados por casi medio siglo: la inauguración (1905) y el reemplazo de la estatua del héroe (1954). Se busca comprender cómo se desarrolló el cambio de sensibilidad de mártir a héroe victorioso respecto al coronel de Arica, lo que legitimó la sustitución de la obra escultórica. Se propone que la imagen de héroe-mártir plasmada en la primera escultura ya era indeseada en la mitad del siglo pasado, frente a la definición de las provincias “cautivas” de Tacna y Arica, el suceso militar peruano en la campaña contra Ecuador (1941) y la promoción de Bolognesi a patrono del Ejército. Además, se refuta la difundida tesis de que hubo un “proyecto primitivo” para el monumento del escultor catalán Agustín Querol, que no se concretizó por intervención de la comisión organizadora del concurso. Se busca interpretar su surgimiento y difusión a luz del contexto de los años 50, cuando se intentaba descalificar la escultura hecha por Querol.

The positions of Peruvian intellectuals and artists upon the monument to Colonel Francisco Bolognesi are presented in two contexts separated for nearly half a century: the inauguration in 1905 and the replacement of the statue of the hero in 1954. The aim is to understand how the change of sen sibility from martyr to victorious hero was developed with respect to the colonel of Arica, which legitimized the substitution of the sculptural work. It is proposed that the image of hero-martyr represented in the first sculpture had already became unwanted in the middle of the last century, because of the definition of the “captive” provinces of Tacna and Arica dispute, the Peruvian military triumph against Ecuador (1941) and the promotion of Bolognesi as a patron of the Peruvian Army. In addition, the widespread thesis that therewas an “primitive project” for the monument, by the Catalan sculptor Agustín Querol, which did not materialize due to the intervention of the organising committee of the competition, is refuted. An interpretation is sought regarding the emergence and dissemination of the “primitive project” in the light of the context of the 1950s, when an attempt was made to disqualify the sculpture made by Querol.
From martyr hero to victorious hero: Peruvian intellectuals in front of the Francisco Bolognesi monument and the thesis of a primitive project for the monument
Keywords: Monumentos; https://purl.org/pe-repo/ocde/ford#6.00.00